(untitled) (Journal of the College of Basic Education, 2024)
Siderophore was extracted from Acinetobacter baumannii isolated from rhizosphere reigion in Baghdad City . The results appeared the ability of isolate (Acinetobacter baumannii 5) to produce Siderophore with diameter of (15) mm and the condition for production was temperature reached 30 degrees, and the optimum pH was 7 . Purification of siderophore through : Ion exchange chromatography for purify more stable form as ferric-siderophore complex and final step through gel filtration. The activity of purified siderophore as antibacterial agent was tested against 13 different local clinical bacterial as follows (Klebsiella pneumoniae ,Pseudomonas aeruginosa ,Acinetobacter baumannii , Escherichia.coli ,Streptococcus pyogenes ,Staph. aureus ,Enterobacter cloacea, Enterobacter aerogenes ,Enterococcus faecalis ,Burkholderia cepacian ,Serratia fiaria ,S. marcescens ,Klebsiella oxytoca ) isolates at concentration 20 mg/ml of free iron siderophore and the results showed that highest activity of siderophore was reported on Streptococcus.pyogenes with inhibition zone (26)mm, and on Acinetobacter baumannii, Serratia.marcescens and Escherichia.coli the inhibition zone was (20)mm while the lowest effects were on Serratia. fiaria and Klebsiella .oxytoca with inhibition zone (16mm). As well as, the purified siderophore showed good activity as antibiofilm of pathogenic bacteria. The highest antiadhesive percentage was observed for Escherichia.coli by percentage 64.4%.